Glycemic management in patients with immune-related diabetes mellitus: A scoping review - Yuan Jiang; Xiaoyan Wang; Lei Lei; Lihua Liu; Danfeng Wu; Siqi Zhang; Dairong Tang; Lingli Fan; Zhou Wen; Xiaojing Xue; Gang Feng (SAGE Open Medicine)
Immune checkpoint inhibitors therapy in cancer patients may induce immune-related diabetes mellitus through islet β-cell destruction, necessitating systematic glycemic management. This scoping review aims to identify and synthesize evidence on glycemic management strategies for immune-related diabetes mellitus. Guided by Arksey and O’Malley’s five-stage scoping review framework, we strictly adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews checklist. A systematic search was conducted across guideline repositories, academic databases, and professional oncology/endocrinology association websites. The search period spanned from database inception to June 30, 2024. Of 5085 initially identified records, 9 studies met inclusion criteria. Evidence was synthesized into five key domains: (1) risk assessment and early detection, (2) therapeutic interventions and monitoring, (3) patient education, (4) glycemic target optimization, and (5) multidisciplinary care coordination. This review consolidates evidence-based best practices for immune-related diabetes mellitus management derived from rigorous methodology. Clinicians should tailor these strategies to individual patient profiles to optimize outcomes while mitigating treatment disruptions.